Evaluation of Culture Time and Media in an In Vitro Testis Organ Culture System. Issue 7 (31st March 2017) - Nakamura, Noriko; Merry, Gwenn E.; Inselman, Amy L.; Sloper, Daniel T.; Del Valle, Pedro L.; Sato, Takuya; Ogawa, Takehiko; Hansen, Deborah K.
Abstract : Background: The complexity of spermatogenesis makes development of appropriate in vitro testis models challenging. A novel in vitro mouse testis culture system has been reported but not yet evaluated as an alternative model for male reproductive toxicity testing. We assessed the effects of media composition on sperm differentiation and testis morphology of cultured mouse testis fragments. Methods: Testes from postnatal day 5 B6:CBA‐Tg( Acrv1 ‐EGFP)2727Redd/J male mice were cultured in knockout serum replacement (KSR) or Albumax I (Albumax) medium. Enhanced green fluorescent protein (EGFP) expression was examined on days 35, 42, 45, and 49 of culture. Histology and flow cytometry were performed for testis morphology and spermatid differentiation. Results: EGFP signals were first observed in round spermatids on day 22 of culture (corresponding to postnatal day 27) and were observed until the end of culture, indicating testis‐specific protein expression. A‐kinase anchor protein 4 expression, a marker of elongated spermatid (step 15–16) occurred earlier in explants cultured in KSR than Albumax medium (typically day 35 and after day 42 of culture, respectively). The percentage of seminiferous tubules with elongated spermatid was higher in Albumax than KSR medium from days 45 to 49 of culture. Conclusion: Albumax medium may facilitate or support better morphology and spermatid production than KSR medium. Further studies need to improve spermatid production and refinement of this in vitro testis culture system that may be useful as a supplement to current male reproductive toxicity testing or an alternative model in cases where in vivo testing may be unfeasible. Birth Defects Research 109:465–474, 2017. © 2017 Wiley Periodicals, Inc.